University Output Soft Skills at Workplace in Blue Economy Strategy for Sustainable Development in Cross River State, Nigeria - Ekanem, Ekpenyong E.; Etor, Comfort R.; Ukpong, Nse N. (Richtmann Publishing, 2020)
This study investigated university output soft skills and blue economy strategy as mechanisms for sustainable development in Cross River State of Nigeria. The study was a descriptive survey research design. The population included all university graduate workers in sea ports in the state. A purposive sampling techniques was used to select 250 respondents from the port locations. The instrument designated ‘Soft Skills In Blue Economy Strategy Questionnaire (SSIBESQ)’ was designed to collect data for the study. The instrument was validated and had a reliability co-efficient of 0.872. The data collected were analyzed using frequency counts and percentage score. The study revealed that university output soft skills were beneficiary to the graduate workers economically and encouraged multitasking in human and material resources for sustainable development of Cross River State, Nigeria. Blue economy strategy, through a dynamic environmental sustainable principles, assisted the university output at workplace. This included to boost new employment, innovation and growth in marine production and other port industries, thereby improving the state economic stand. Some of the recommendations made were: universities should give more attention to soft skills development, government should support policies on university output soft skills and blue economy strategy as sine-qua-non for utilization of business opportunities and economic development in the state.